Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1753-0407.12658
|View full text |Cite
|
Sign up to set email alerts
|

Glucose excursions and hypoglycemia in patients with type 2 diabetes treated with mitiglinide/voglibose versus glimepiride: A randomized cross‐over trial

Abstract: Background: Glucose excursions and hypoglycemia are associated with cardiovascular complications. However, no studies have evaluated glucose excursions and the frequency of hypoglycemia in patients treated with mitiglinide/voglibose versus glimepiride as add-on to dipeptidyl peptidase-4 inhibitor therapy. Methods: This cross-over trial included 20 patients with type 2 diabetes. After initiating vildagliptin 100 mg, patients were randomly assigned to receive mitiglinide 10 mg/voglibose 0.2 mg three times daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Other indices of glycemic variability, such as SD and CV, were also significantly lower for mitiglinide/voglibose. Fujimoto et al 14 . compared the effects of mitiglinide/voglibose and glimepiride (1.0 mg/day) using a crossover design, similar to our study, and reported that MAGE for mitiglinide/voglibose was 62.46 mg/dL, significantly lower than for glimepiride (95.04 mg/dL).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other indices of glycemic variability, such as SD and CV, were also significantly lower for mitiglinide/voglibose. Fujimoto et al 14 . compared the effects of mitiglinide/voglibose and glimepiride (1.0 mg/day) using a crossover design, similar to our study, and reported that MAGE for mitiglinide/voglibose was 62.46 mg/dL, significantly lower than for glimepiride (95.04 mg/dL).…”
Section: Discussionsupporting
confidence: 85%
“…One previous study of 20 patients described a significant difference in glycemic variability between mitiglinide/voglibose and glimepiride 14 , but no previous studies have investigated vascular endothelial function. Therefore, the aim of our study was to conduct exploratory evaluation of the assessment parameters, and a sample size of 30 cases was determined as feasible within the planned registration period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily blood glucose curve with PB-201 had a similar shape but shifted downwards compared with placebo, indicating that PB-201 may have an impact on fasting glucose rather than postprandial glucose. This trajectory is in contrast with the flattened curve under treatment with mitiglinide/voglibose, which lowered glucose fluctuations postmeal [32]. The mechanism of action behind this may be PB-201's constant activation of glucokinase in the liver.…”
Section: Tablementioning
confidence: 84%
“…Based on the pharmacological mechanism, it is unlikely that an α-glucosidase inhibitor alone can induce hypoglycemia. The incidence of hypoglycemia with voglibose alone is lower than that with other antidiabetic drugs [ 23 , 24 ]. In this case, there were no complications, such as other diseases and infections, and the patient was consuming food without any problems.…”
Section: Discussionmentioning
confidence: 99%